PENINGKATAN EFEKTIVITAS PENANGANAN KARGO IMPOR UDARA - Ricky Ricardianto; Hasrat Syaputra (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
Internal Factors of SWOT analysis which is owned by PT. Birotika Universe / DHL Express consists of force among other warehouse clean, have adequate storage equipment, warehouse have the competitive rental rates, the maximum service to the customer, and have a professional management with a score of (1.800). PT. Birotika Universe / DHL Express is located in quadrant I. In this area the company has a favorable situation because the company has the opportunity and strength. This means that the company can use its power to take advantage of opportunities- opportunities that exist. The strategy used is to support aggressive growth policy.